Role of quorum sensing-based regulation in development of anaerobic ammonium oxidation process. (January 2023) - Yang, Jun-Hui; Huang, Dong-Qi; Geng, Yin-Ce; Ling, Yi-Rong; Fan, Nian-Si; Jin, Ren-Cun
Graphical abstract: Highlights: Fast start-up of anammox process was achieved with a mixture of activated sludge. The maximum nitrogen removal rate of anammox reactor was 1.14 g N L −1 d −1 . Candidatus Brocadia was more competitive under high-strength substrate condition. Quorum sensing potentially contributed to the start-up of anammox process. Abstract: Shortage of anaerobic ammonium oxidation (anammox) sludge greatly limits the extensive full-scale application of anammox-based processes. Although numerous start-up strategies have been proposed, the interaction among microbial consortia and corresponding mechanism during the process development remain unknown. In this study, three reactors were established based on different seed sludges. After 27 days, the anammox process inoculated with anammox granules and activated sludge (1:5) was firstly achieved, and the highest nitrogen removal rate was 1.17 kg N m −3 d −1 . Correspondingly, the anammox activity and abundances of related functional genes increased. Notably, the dominant anammox bacteria shifted from Candidatus Kuenenia to Candidatus Brocadia. Metagenomic analysis indicated that quorum sensing-based regulation mainly contributed to the proliferation and accumulation of anammox bacteria. This work provides an insight into the quorum sensing (QS)-regulated microbial interactions in the anammox and activated sludge consortia during the process development.